Enhancing Transformative Learning through 'Setara Daring': A Framework for Optimizing Equivalent Education in Bandung, Indonesia - Saripah, Iip; Pramudia, Joni Rahmat; Ardiwinata, Jajat S; Boriboon, Gumpanat (Journal of Nonformal Education, 2025)
Background: Transformative learning is a learning process that 'brings' learners closer to reality, presenting critical-reflective knowledge, by positioning the teacher more as a facilitator to guide and encourage that process. Online learning has become a choice for face-to-face learning systems in the Digital Era using Learning Management Systems (LMS) to support learning achievements.Research Objectives: The ultimate goal to be achieved in this research is the emergence of a new product on the transformative learning model assisted by the LMS "Setara Daring" for learners of Equivalency Education in the city of Bandung, IndonesiaResearch Method: This research employs a qualitative approach utilizing the case study method to explore the implementation of transformative learning through the Setara Daring LMS in equivalency education. The qualitative approach is chosen to gain an in-depth understanding of the learning process, interactions, and experiences of learners and educators in a digital learning environment. The case study method enables a comprehensive and context-specific analysis by examining real-world applications of the LMS in non-formal education units in Bandung City. Data collection techniques include observations, in-depth interviews, and document analysis, ensuring a holistic examination of the learning dynamics. Through this approach, the study aims to capture the nuances of learner engagement, critical thinking development, and the role of facilitators in guiding transformative learning. The qualitative nature of this research allows for an exploratory and interpretive analysis, providing valuable insights into how LMS-supported transformative learning can enhance the critical attitudes and adaptability of learners in non-formal education settings. Research Findings: The findings of this study highlight the crucial role of the Setara Daring Learning Management System (LMS) in fostering a transformative learning experience within the context of equivalency education. The system effectively promotes active learner engagement through structured yet flexible learning pathways, enabling meaningful interactions between students, instructors, and learning materials. Interactive features such as discussion forums, collaborative assignments, and formative assessments further reinforce knowledge construction and participation. Additionally, the LMS facilitates critical reflection by integrating activities that encourage students to analyze, evaluate, and synthesize information critically, supported by immediate feedback and self-paced learning opportunities. Through guided discussions and problem-solving tasks, learners are empowered to question assumptions, articulate reasoning, and engage in higher-order thinking processes. Moreover, the Setara Daring LMS enhances critical thinking skills by incorporating inquiry-based learning strategies, case studies, and self-assessment tools, fostering an environment that supports independent exploration, analytical reasoning, and decision-making abilities. Overall, this study provides empirical evidence that Setara Daring LMS serves as an effective platform for cultivating interactive, reflective, and cognitively engaging learning experiences, contributing to the advancement of digital learning innovations in non-formal education..Research Conclusion: This study demonstrates that the Setara Daring LMS effectively supports active learner engagement, critical reflection, and critical thinking skills in equivalency education. The developed transformative learning model, facilitated by this LMS, offers an interactive and flexible approach, helping learners adapt to online learning in the digital era. Educators play a vital role as facilitators, guiding learners' critical thinking processes. The Setara Daring LMS has proven to be an effective tool for improving learning quality in non-formal education in Bandung City. This research contributes to a transformative learning model based on LMS, providing a foundation for further development and application of LMS to enhance learning quality in non-formal education.Research Novelty: The novelty of this study lies in its development of a transformative learning model using the Setara Daring LMS for equivalency education, a sector often overlooked in digital learning innovations. It highlights the LMS's effectiveness in fostering active engagement, critical reflection, and critical thinking skills, while emphasizing the crucial role of educators as facilitators in guiding learners. The research provides empirical evidence from its implementation in Bandung City's non-formal education system, offering a foundational framework for future LMS-based learning models in non-formal education. This study bridges the gap between digital tools and transformative learning in under-researched educational contexts.